Fibonacci-type tubular photobioreactor for the production of microalgae. (November 2019) - Díaz, Juan Pablo; Inostroza, Cristian; Acién Fernández, F.G.
Graphical abstract: Highlights: A new tubular photobioreactor design following the Fibonacci equation has been proposed. The proposed design allows up to a 1.4-times increase in intercepted solar radiation compared to horizontal surface. The proposed design allows to achieve up to 8.6% solar efficiency at outdoor conditions. The reliability of the reactor for the outdoor production of Spirulina has been demonstrated. Abstract: In this work, a new tubular photobioreactor design based on the Fibonacci equation is proposed. A small 6 L unit was evaluated indoors and a larger 250 L unit was evaluated outdoors; both units maintained the same concept and the same aspect ratio. To test the new design, the Arthrospira ( Spirulina ) platensis strain was used. The results show that the proposed design allows the temperature, pH and dissolved oxygen to be maintained within the optimal ranges recommended for the selected strain. Consequently, overheating was avoided, even under outdoor conditions, and the dissolved oxygen concentration remained below the 200%Sat limit. Modelling of the growth in both reactors demonstrated that cell performance was optimal under indoor and outdoor conditions, with outdoor maximal specific growth rates reaching 0.8 1/day. Moreover, under outdoor conditions, photosynthetic efficiency reached 8.3%, thus confirming high light-utilization efficacy even at high irradiances when using this new photobioreactor design. Our work represents a first step in the development of this promising technology as an alternative to those presently used. Developing industrial-scale microalgae biotechnology requires more productive and effective photobioreactors capable of maximizing biomass productivity under high light conditions.